Medical Equipment And Medication Inventory Information System At West Citarip Puskesmas Is Based On A Website - Puji Nurmalik Ibrahim; Rinawati Rinawati (LPPM STMIK Mardira Indonesia, 2023)
An inventory information system offers data from many processes, including purchasing, storing, and reporting. As a result, it is essential to create an application for the Inventory Information System to transform the company's performance process from manual to automated, resulting in more thorough reports. Data collection, system design, system analysis, and database system design are used to create this application. It is creating PHP-based application programs. MYQSL is the database used, while VisualStudio Code is used for development scripts. It has been determined that the West Citarip Health Center's Drug and Medical Device Inventory Information System is ready to be designed and implemented.